UPAYA KEPALA SEKOLAH DALAM MENINGKATKAN KEGIATAN BELAJAR MENGAJAR DI SEKOLAH MENENGAH KEJURUAN TAKWA BELITANG KABUPATEN OKU TIMUR - Alamsyah; Taqwatul Uliyah; Nurwidi Astuti (UNISAN JURNAL, 2023)
In modern education, there is an independent special supervisor, but a principal can also be a supervisor to supervise and assist teachers in learning daily tasks. For this reason, the principal must have the knowledge and ability to become a supervisor so that the process of teaching and learning activities runs smoothly. From the explanation above, it can be used as a reference to improve the quality of teaching and learning activities (KBM), so that school graduates in Indonesia can be qualified and can compete with neighboring countries. To improve the quality of education in schools, the principal’s efforts in improving the quality of education or KBM are very necessary, because the principal is a leader, supervisor and educator. Of the three words, a school principal must be able to improve the quality of education or kbm. This research uses descriptive type qualitative research methods. The informants in this study were the Head of the Madrasa, Teachers and students. Data collection techniques use observation, interviews, and documentation studies. Test the validity of the data with increased persistence in the study and using reference materials. The conclusions that can be drawn from the Principal’s Efforts in Improving the Quality of Teaching and Learning Activities (KBM) are as follows: The principal of Sekolah Menengah Kejuruan Takwa Belitang Kabupaten Oku Timur, always strives to improve the quality of kbm, with efforts such as: Always strive for teachers according to their respective competencies. Always provide coaching/motivation to students. Always strive for adequate learning infrastructure Always supervise the running of KBM The supporting and inhibiting factors in improving the quality of kbm in Sekolah Menengah Kejuruan Takwa Belitang Kabupaten Oku TimurDistrict are: Supporting factors in seeking to improve the quality of KBM are as follows: The principal always focuses on his work There is a solid and compact cooperation between the principal, teachers and employees. The inhibiting factors in seeking to improve the quality of kbm are as follows: There are still teachers who lack discipline, such as being late for school, late for class. Relatively minimal education funding From the efforts made by the principal, it can be concluded that the principal of Sekolah Menengah Kejuruan Takwa Belitang Kabupaten Oku TimurDistrict, has always sought to improve the quality of kbm.